Development of E-Module Based on Experiential Learning to Empower Student’s Environmental Literacy Abilities in Biology Lessons - Kusuma, Latifatul Nararia; Sholihah, Mar'atus; Malahayati, Eva Nurul (Universitas Tidar, 2025)
The growth of the human population increases production and consumption, leading to higher waste volumes. Environmental literacy is essential to broaden knowledge, foster responsibility, and enhance students’ ability to solve environmental problems. This study aims to assess the feasibility and practicality of an experiential learning-based e-module to strengthen environmental literacy skills in grade X high school biology. Using the Thiagarajan 4D R&D model (define, design, develop, disseminate), the module was tested on 33 grade XI-2 students of SMAN 1 Kademangan. Data were collected through validation and teacher and student response questionnaires. The results showed that the e-module met the criteria of validity, reliability, completeness of material, accuracy of facts and data, and effectively encouraged environmental literacy improvement. The module was found to be efficient and accurate in measuring students’ skills. Trial results and questionnaire responses indicated significant improvements in environmental literacy test scores and positive feedback from both teachers and students. Therefore, the experiential learning-based e-module is considered suitable and practical for use in teaching biology, particularly in fostering environmental literacy among grade X high school students.